2001
DOI: 10.1038/85499
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus nuclear protein EBNA-3C interacts with the human metastatic suppressor Nm23-H1: A molecular link to cancer metastasis

Abstract: Epstein-Barr virus (EBV) is an oncogenic virus associated with a number of human malignancies including Burkitt lymphoma, nasopharyngeal carcinoma, lymphoproliferative disease and, though still debated, breast carcinoma. A subset of latent EBV antigens is required for mediating immortalization of primary B-lymphocytes. Here we demonstrate that the carboxy-terminal region of the essential latent antigen, EBNA-3C, interacts specifically with the human metastatic suppressor protein Nm23-H1. Moreover, EBNA-3C reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
150
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 35 publications
8
150
0
Order By: Relevance
“…Recently, Subramanian et al (2001) reported that the Epstein-Barr virus encoded protein EBNA-3C interacts speci®cally with nm23-H1, and that this interaction reversed the ability of nm23-H1 to suppress migration of Burkitts lymphoma and breast carcinoma cells. This is the ®rst evidence that a DNA tumour virus may target a cellular protein associated with metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Subramanian et al (2001) reported that the Epstein-Barr virus encoded protein EBNA-3C interacts speci®cally with nm23-H1, and that this interaction reversed the ability of nm23-H1 to suppress migration of Burkitts lymphoma and breast carcinoma cells. This is the ®rst evidence that a DNA tumour virus may target a cellular protein associated with metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, We have previously reported at length about an association between Nm23-H1 and the essential Epstein-Barr virus nuclear antigens (EBNA) 1 and 3C. 41,56,57 In those reports, we have shown that Nm23-H1 predominant cytoplasmic localization was dramatically changed to nuclear signals when Nm23-H1 was coexpressed with either EBNA1 or EBNA3C. 41,56 We are currently addressing whether viral proteins such as EBNA1 and EBNA3C, especially EBNA3C shows B cell transformation activity, 1 affect the localization and the function of Nm23-H1, as it relates to signaling through the Rho family GTPase protein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The migrated cells were counted at sites in each wells at 40x with an Olympus BX40 light microscope. 56 The data presented at each concentration is the mean of three separate experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The current work builds on a voluminous but inconclusive history of potential mechanistic pathways for metastasis suppression by the NME (NM23, nucleoside diphosphate kinase, AWD) family. Considerable evidence indicates that protein:protein interactions with NME modulate components of the metastatic process and in vivo metastasis ( [52][53][54] as examples). The role of NME enzymatic activities has been less certain.…”
Section: Discussionmentioning
confidence: 99%